Mordida cruzada anterior: revisão da literatura - Ferreira, Carolina Alves [UNESP] (2013)
The anterior crossbite is a malocclusion characterized by a negative overjet, and may involve one or more teeth. This malocclusion may be dentoalveolar, skeletal or functional, and the etiological factors that contribute to it's occurrence range from premature contacts, prolonged retention of deciduous teeth to genetic inheritance. The role of the general practitioner in the detection of this malocclusion in children, both in the primary and mixed dentitions is crucial to the success of treatment and also in reducing sequelae left by it. Among the treatment modalities are dental movements towards buccal (upper teeth) and lingual (lower teeth), with inexpensive and simple appliances to movements involving a displacement of the skeletal portion of the maxilla, with a poor prognosis. Considering the intimate relationship between nature of malocclusion, type of treatment and prognosis of results, the general practioner gain prominence in the early identification and treatment, or even in the correct time to indicate a specialist. The objective of this study is to describe, by means of literature review, the main points related to anterior crossbite in children, and present a case to illustrate one way of treatment of dentoalveolar anterior crossbite